Analisis Pengaruh NPM, ROE DAN FIRM SIZE terhadap Nilai Perusahaan dengan GCG sebagai Variabel Intervening - Ronald M. Purba; Embun Prowanta (Sekolah Pascasarjana Perbanas Jakarta, 2020)
The research objective was to examine the effect of Return On Equity (ROE) and Net Profit Margin (NPM and Firm Size on the company value (Price Book Value) with Good Corporate Governance (GCG) as an intermediate variable (Intervening). The research population was 77 companies based on The Indonesian Institute for Corporate Governance (IICG). One of the criteria used is the most trusted company and trusted company by The Indonesian Institute for Corporate Governance (IICG) during 2010 – 2018. Five companies meet the requirements as a sample of the total population meets the criteria. The method used is path analysis with the test equipment using Smart PLS (Partial Least Square). The test results show that ROE has a significant negative effect on GCG and ROE positively and significantly affects firm value (PBV). NPM does not affect GCG, and NPM has a negative and significant effect on PBV, while Firm size has a positive and significant effect on GCG, and Firm size has no effect on PBV. GCG has a positive and significant effect on PBV. GCG cannot mediate the effect of ROE on PBV, and GCG is not able to mediate the effect of NPM on PBV, while GCG is significantly able to mediate the effect of Firm Size on PBV.